Body image disturbances in NCAA Division I and III female athletes - Kato, K.; Jevas, S.; Culpepper, D. (The Sport Journal, 2011)
Abstract The purpose of this study was to examine and compare eating characteristics and body image disturbances in female NCAA Division I and III athletes in the mainstream sports of basketball, softball, track/cross country, volleyball, soccer, tennis, swimming/diving, and ice hockey. Female collegiate athletes (N = 118) from Division I and III universities completed the EAT-26 and MBSRQ. Personal demographics and anthropometric data including height, weight, BMI and Body Fat estimates were also assessed. The study found that 49.2% (Division I) and 40.4% (Division III) of female athletes were in the subclinical eating disorder range. Results assessing body satisfaction, reported that 24.2% of Division I female athletes and 30.7 % of Division III female athletes were either very dissatisfied or mostly dissatisfied with their overall appearance. Results also showed that Division I female athletes were less satisfied with their appearance evaluation (body areas satisfaction, and lower torso). Division III female athletes reported higher levels of bulimic behaviors and weight preoccupation. The results indicate that athletes in refereed female sports are at risk for eating disorders, and that body image risk factors vary between NCAA competition divisions. This research provides sport professionals with a better understanding of risk factors influencing the prevalence of eating disorders between female athletes` divisional competition levels.